Initial Reports of the Deep Sea Drilling Project 1986
DOI: 10.2973/dsdp.proc.92.130.1986
|View full text |Cite
|
Sign up to set email alerts
|

B, Li, and Associated Trace Element Chemistry of Alteration Minerals, Holes 597B and 597C

Abstract: B, Li, and other trace elements were analyzed in samples from 12 celadonite and smectite-rich veins from oxidative and non-oxidative alteration zones in basalts from Holes 597B and 597C. The oxidative alteration zones are characterized by celadonite and Fe-oxyhydroxide and conspicuously high K, Rb, and B concentrations. In contrast, the non-oxidative alteration zones are characterized by Mg-rich smectite (saponite), talc, and calcite and high Li concentrations. Neither B nor Li reaches high concentrations in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Li is considered to be a mobile element during reaction of seawater with basalt at temperatures greater than 70°C (Seyfried et al, 1984); it is leached from basalt altered at moderate to high temperature. Evidence from dredged and drilled basalts from shallow in the crust suggests that Li is taken up from seawater into secondary alteration products under low temperature (0°-50°C) seafloor weathering conditions (Berndt and Seyfried, 1986;Ryan and Langmuir, 1987). Li concentrations in the borehole fluids show an excellent correlation with Mg (Fig 21).…”
Section: Water/rock Mass Ratiosmentioning
confidence: 95%
“…Li is considered to be a mobile element during reaction of seawater with basalt at temperatures greater than 70°C (Seyfried et al, 1984); it is leached from basalt altered at moderate to high temperature. Evidence from dredged and drilled basalts from shallow in the crust suggests that Li is taken up from seawater into secondary alteration products under low temperature (0°-50°C) seafloor weathering conditions (Berndt and Seyfried, 1986;Ryan and Langmuir, 1987). Li concentrations in the borehole fluids show an excellent correlation with Mg (Fig 21).…”
Section: Water/rock Mass Ratiosmentioning
confidence: 95%
“…Previous workers have suggested that uptake of Li in basalt during seafloor alteration is tied to the stabilization of secondary minerals such as smectite (saponite), celadonite, and phillipsite, with Li residing in octahedral sites in suitable phases (Chan et al, 2002;Vigier et al, 2008). Major and trace element analyses of these minerals in various modern sedimentary and altered basalt settings indicate that the LILE tend to be incorporated into interlayer sites in illite/celadonite (perhaps also K-rich phillipsite), whereas Li is more concentrated in Mg-rich phases such as saponite and other K-poor smectite phases (see Desprairies et al, 1984;Berndt and Seyfried, 1986;Heling et al, 1992;Porter et al, 2000). Varying relative modal abundances of these phases, among a suite of samples from the same site, would result in a general lack of correlation between concentrations of Li and LILE in the same rocks, whereas the LILE would tend to show co-enrichments because of their general similarity in geochemical behavior (see Fig.…”
Section: Fluid-mediated Addition Of LI To Metamafic Rocksmentioning
confidence: 97%
“…Bulk compositional trends documented in the preceding section, however, do indicate qualitative water/rock conditions. At lowtemperatures, mobile elements such as Rb and K are removed from seawater and incorporated into secondary phases [Richardson et al, 1980;Staudigel et al, 1981;Seyfried et al, 1984;Berndt and Seyfried, 1986]. Water/rock ratios may be calculated using bulk rock compositions if it is assumed that the difference between fresh and altered rock values reflects the amount of seawater seen by the rocks.…”
Section: Fluid Flow and Water/rock Ratiosmentioning
confidence: 99%